Addressing information and credit barriers to making India open defecation free and improving child health: Evidence from a cluster randomized trial in rural India - Payal Seth; Prabhu Pingali (PLoS ONE, 2025)
Background Open defecation (OD) remains a significant public health challenge in India, contributing to adverse child health outcomes. Eliminating OD and improving child health necessitates both universal access and adoption of toilets. Despite the success of removing credit constraints and enhancing access to subsidized toilets through national sanitation campaigns, the adoption of these toilets is still lagging in India. This is because households might also be lacking information about the benefits of using toilets (information constraint). Methods In this paper, we test for the joint efficacy of the removal of information and credit constraints versus solely addressing the credit constraint at eliminating OD, based on a cluster randomized control trial in rural India. We implemented two interventions: a universal community-led behavior change campaign along with subsidized construction of individual household toilets for every household that opted for subsidy (cluster A) and only subsidized construction of individual household toilet construction for every household that opted for the subsidy (cluster B). No behavior change was provided in cluster B. The control group did not receive any intervention. Results We find that the removal of information and credit constraints at a near-universal level in cluster A resulted in improved toilet access and adoption, eliminating OD at the community level, with a significant gain in child weight-for-age z-scores (WAZ scores). There was an increase in the percentage of households that owned individual household toilets from 2% to 98% and a decline in female respondents practicing OD from 98% to 4% in cluster A. In cluster B, ownership of individual household toilets improved by 78 percentage points (from 6% to 84%), but OD decreased by only 45 percentage points (from 95% to 50%) for the respondents. The control group saw no significant changes. For children under five, there was a statistically significant increase in WAZ scores by 0.68-0.69 standard deviations in cluster A, while cluster B showed insignificant changes when compared to the control group. Conclusions The study implies that supplementing universal financial support with community-level information intervention enhances sustainable adoption of improved sanitation facilities, aiding India’s progress towards an open defecation-free nation and improving child health outcomes.